Children's Environmental Health Indicators for Low- and Middle-Income Countries in Asia - Eun Mi Jung; Eun Mee Kim; Minah Kang; Fiona Goldizen; Fiona Gore; Marie Noel Brune Drisse; Eun Hee Ha (Ubiquity Press, 2017)
Background: Given that low- and middle-income countries (LMICs) in Asia still have high child mortality rates, improved monitoring using children's environmental health indicators (CEHI) may help reduce preventable deaths by creating healthy environments. Objectives: Thus, the aim of this study is to build a set of targeted CEHI that can be applied in LMICs in Asia through the CEHI initiative using a common conceptual framework. Methods: A systematic review was conducted to identify the most frequently used framework for developing CEHI. Due to the limited number of eligible records, a hand search of the reference lists and an extended search of Google Scholar were also performed. Based on our findings, we designed a set of targeted CEHI to address the children's environmental health situation in LMICs in Asia. The Delphi method was then adopted to assess the relevance, appropriateness, and feasibility of the targeted CEHI. Findings: The systematic review indicated that the Driving-Pressure-State-Exposure-Effect-Action framework and the Multiple-Exposures-Multiple-Effects model were the most common conceptual frameworks for developing CEHI. The Multiple-Exposures-Multiple-Effects model was adopted, given that its population of interest is children and its emphasis on the many-to-many relationship. Our review also showed that most of the previous studies covered upper-middle- or high-income countries. The Delphi results validated the targeted CEHI. The targeted CEHI were further specified by age group, gender, and place of residence (urban/rural) to enhance measurability. Conclusions Improved monitoring systems of children's environmental health using the targeted CEHI may mitigate the data gap and enhance the quality of data in LMICs in Asia. Furthermore, critical information on the complex interaction between the environment and children's health using the CEHI will help establish a regional environmental children's health action plan, named "The Children's Environment and Health Action Plan for Asia."